Double-shot MeV electron diffraction and microscopy - P. Musumeci; D. Cesar; J. Maxson (Structural Dynamics, 2017)
In this paper, we study by numerical simulations a time-resolved MeV electron scattering mode where two consecutive electron pulses are used to capture the evolution of a material sample on 10 ps time scales. The two electron pulses are generated by illuminating a photocathode in a radiofrequency photogun by two short laser pulses with adjustable delay. A streak camera/deflecting cavity is used after the sample to project the two electron bunches on two well separated regions of the detector screen. By using sufficiently short pulses, the 2D spatial information from each snapshot can be preserved. This “double-shot” technique enables the efficient capture of irreversible dynamics in both diffraction and imaging modes. In this work, we demonstrate both modes in start-to-end simulations of the UCLA Pegasus MeV microscope column.